Profiling sediment bacterial communities and the response to pattern-driven variations of total nitrogen and phosphorus in long-term polyculture ponds - Zhang, Yan; Li, Tiejun; Li, Guangzhi; Yuan, Tao; Zhang, Yao; Jin, Lei (Frontiers in Marine Science, 2024)
Sediment bacterial communities are decisive drivers of nutrient cycling processes in aquaculture ecosystems and are readily affected by surrounding environmental factors. However, the knowledge of sediment nutrient accumulations and bacterial community structure is limited in the emerging polyculture systems. Herein, we investigated the profiles of sediment properties and bacterial communities in six typical polyculture ponds and primarily explored the influence of total nitrogen and phosphorus on the bacterial species and diversity. In almost all sediment samples, Proteobacteria, Chloroflexi, and Bacteroides were the dominant species at the phylum level, and the five most abundant bacterial genera were Sulfurovum, Woeseia, Ilumatobacter, Robiginitalea, and Cyanobium_PCC-6307. A clear different bacterial community was observed with the most dominant bacterial phylum Firmicutes and the lowest bacterial diversity in TZ1 pond sediment; meanwhile, the TZ1 pond also showed the highest TN and TP concentrations. Notably, sediments from WZ1 and WZ2 ponds in low-latitude regions exhibited higher bacterial richness and diversity. Based on Pearson’s correlation analysis, bacterial α-diversity indices showed significant negative correlation with sediment TP content, and TN content contributed the most to the abundance of sediment dominant bacterial genus, indicating that the bacterial community is highly associated with sediment nutrient concentrations. Moreover, co-occurrence network analysis further revealed some keystone taxa that exhibited high correlations with other bacterial species, especially the high-abundance genus Robiginitalea bridging a large number of connections. Compared to traditional mono-mariculture pattern, our study provided direct evidence of lower nutrient loadings and different bacterial communities in the polyculture ponds. This could assist polyculture practitioners in developing effective strategies for detailed nutritional management.